ANALISIS RASIO KEUANGAN DAERAH SEBAGAI PENILAIAN KINERJA PADA PEMERINTAHAN KOTA MAGELANG - Salwa Qur'ani; Endang Kartini Panggiarti (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
This study aims to analyze the financial performance of the local government of the City of Magelang by using the analysis of independence ratios, effectiveness ratios, efficiency ratios, hardness ratios and growth ratios. The type of research in this research is quantitative. The data used in this study are secondary data in the form of the Magelang City Government Financial Statements for 2015-2019 which were obtained using documentation techniques. The results of this study indicate that the independence ratio of 38.73% is low / not independent, the effectiveness ratio of 110.85% is classified as effective, the efficiency ratio of 100.22% is classified as inefficient, the compatibility ratio / shopping activity is classified as inefficient. Operational expenditure ratio of 87.16% and capital expenditure ratio of 24.66% are classified as less harmonious, and growth ratio of 10.16% is classified as low. The implication of the results of this study is that the City of Magelang must continue to increase and optimize local revenue by managing unprocessed regional resources and the government must also be able to prioritize its allocation of funds in optimal budget and development spending. Penelitian ini bertujuan untuk menganalisis kinerja keuangan pemerintah daerah Kota Magelang dengan menggunakan analisis rasio kemandirian, rasio efektivitas, rasio efisiensi, rasio keserasihan dan rasio pertumbuhan. Jenis penelitian dalam penelitian ini adalah kuantitatif. Data yang digunakan dalam penelitian ini adalah data sekunder berupa Laporan Keuangan Pemerintah Kota Magelang tahun 2015 – 2019 yang diperoleh dengan menggunakan teknik dokumentasi. Hasil penelitian ini menunjukkan bahwa rasio kemandirian 38,73% tergolong rendah / tidak mandiri, rasio efektivitas 110,85% tergolong efektif, rasio efisiensi 100,22% tergolong tidak efisien, rasio keserasian / aktivitas belanja tergolong tidak efisien. Rasio belanja operasional 87,16% dan rasio belanja modal 24,66% tergolong kurang harmonis, dan rasio pertumbuhan 10,16% tergolong rendah. Implikasi hasil penelitian ini adalah bahwa Kota Magelang harus terus meningkatkan dan mengoptimalkan pendapatan asli daerah dengan cara mengelola sumber daya daerah yang belum diolah selama ini dan pemerintah juga harus dapat mengprioritaskan alokasi dananya pada belanja ritun dan belanja pembangunan secara oprimal.